Trends in sports participation in adolescents: Data from a large-scale sample in the US adolescents - Deng, Yu; Fan, Anhui (Frontiers in Public Health, 2022)
Background: Although changes in overall PA have been identified in adolescents, the trend in sports participation is still understudied. It is widely believed that monitoring the changes in sports participation is conducive to promoting the development of sports activities. The purpose of this research is to identify the changes in sports participation in adolescents over the past year. Methods: This research selected secondary data from 2011, 2013, 2015, 2017, and 2019 Youth Risk Behaviour Surveillance. Logistic regression models were applied to discuss and analyze the secular changes across the years of data. The change differences in sports participation by sex, grade, and race/ethnicity were also explored via separate logistic regression. Results: A declined overall trend could be observed in sports participation in adolescents. The declined trend was also observed in 10th and 12th-grade adolescents, and an increase could be observed in 11th-grade adolescents, but few changes were found in 9th-grade adolescents. Only white adolescents reported an increasing prevalence of sports participation, the slight declines in sports participation were observed in black or African American, Hispanic/Latino, and other adolescents. Conclusions: The declined trend in sports participation could be seen in adolescents between 2011 and 2019.